Business Process Management Workshops BPM 2005 International Workshops, BPI, BPD, ENEI, BPRM, WSCOBPM, BPS, Nancy, France, September 5, 2005. Revised Selected Papers - Bussler, Christoph; Haller, Armin (Information Systems and Applications, incl. Internet/Web, and HCI, 2006)
Six parallel Business Process Management workshops were held on September 5th, 2005, in conjunction with the Third International Conference on Business Process Management (BPM 2005) in Nancy, France. This was the first time BPM had asso- ated workshops, and the workshop program was a great success. The topics of the workshops ranged from fundamental process modeling primitives to the recently emerged field of Web service choreography and orchestration, rep- sented in the "Workshop on Business Processes and Services" and the "Workshop on Web Service Choreography and Orchestration;" a topic which intersects the research fields of business process management and Web services. Another strong focus was on business process design and business process intelligence, emerging areas that have gained increasing importance in supporting business process reengineering to derive superior process designs. These topics were covered in the respective wo- shops. A widely discussed topic in several sessions was business process interoperability in the workshop on "Enterprise and Networked Enterprises Interoperability." Finally, the last workshop in these proceedings called "Business Process Reference Models" aimed at discussing different views on reference models in order to come to a c- mon understanding of the terms involved. We would like to thank the workshop organizers for their efforts in the workshop preparation, the organization of the review process, the exciting workshop programs and their management onsite and for their cooperation in the post-publication process.